The development of physiological profiles and identification of training needs in NCAA female collegiate rowers using isoperformance curves - Fukuda, D. H.; Kendall, K. L.; Smith, A. E.; Dwyer, T. R.; Stout, J. R. (European Journal of Applied Physiology, 2011)
The purpose of this study was to propose a systematic method for the identification of training strategies and team selection using isoperformance curves. Rowing is a sport that relies on both aerobic and anaerobic energy contributions during a standard 2,000 m competition. The critical velocity model combines both aerobic (critical velocity, CV) and anaerobic (anaerobic rowing capacity, ARC) parameters in a single two-dimensional graphic display. The concept of isoperformance curves, a series of linear equations corresponding to minimum performance standards, allows for an objective overview of a large group of athletes of varying talent. The purpose of this study was to develop physiological profiles from the CV test, and to evaluate results with isoperformance curves to identify training strategies for collegiate rowers. Thirty-five female collegiate rowers completed four time trials over various distances (400, 600, 800, and 1,000 m). CV and ARC were calculated and compared between novice and varsity athletes. CV values for the varsity group were significantly higher than the novice group (P = 0.016). No significant differences were found between groups for ARC (P = 0.068). Mean and individual CV and ARC values were plotted on the x- and y-axes, respectively, and junior, collegiate, and elite isoperformance curves were developed using 2,000 m times from recent indoor rowing competitions. Stratification of athletes through isoperformance curves was used to identify specific training interventions (anaerobic and/or aerobic) needed to improve their 2,000 m performance. The information drawn from isoperformance curves and the parameters of the CV test can be used to provide an objective view of physiological capabilities and training needs on both an individual and team basis.